TINGKAT KEPUASAN KONSUMEN TERHADAP PRODUK AMPLANG XYZ DI KELURAHAN SARIJAYA KECAMATAN SANGA-SANGA - Rabbaniyatus Syakhshiyah; Elly Purnamasari; Heru Susilo (2339-1324, 2023)
Amplang XYZ is processing bussiness using milkfish (Chanos chanos) as primaryi ngrediemt . The purposes of the study were to: 1) analyzing consumer characteristics; 2) measuring CSI; 3) identifying the attributes that to improved a quality in Amplang XYZ. The study conducted from June 2021 to September 2021. Sampling method was non probability sampling with 50 respondents by using accidental and purposive samplings. Analysis method employed descriptive analysis, CSI, Importance Performance Analysis (IPA). The results of this study showed that the majority of Amplang XYZ consumer were 17-23 years old female, senior highschool graduated with married marital status and student with income range monthly less than Rp.500.000. CSI of Amplang XYZ was 73,63%, which mean overall Amplang XYZ consumer were satisfied of the amplang attributes, but some attributes that to improved i.e the clarity of the halal and the clarity of the expired Keywords : Amplang XYZ, consumer characteristics, customer satisfaction, product attributes ABSTRAK Amplang XYZ adalah usah